Genetic Polymorphisms and Platinum-Based Chemotherapy-Induced Toxicities in Patients With Lung Cancer: A Systematic Review and Meta-Analysis - Liu, Wenhui; Wang, Ying; Luo, Jianquan; Yuan, Haiyan; Luo, Zhiying (Frontiers in Oncology, 2020)
Background: Platinum, including cisplatin, carboplatin and oxaliplatin, is indispensable for treatment of lung cancer. Development of toxicity frequently necessitates dose reduction or discontinuation of therapy, despite clinical response. Pharmacogenomics studies were reviewed for identification of genetic variants possibly underlying individual susceptibility to platinum related toxicities. Method: We conducted a systematic search in Pubmed and Embase for pharmacogenomics reports with focus on commonly reported platinum-induced toxicities, such as gastrointestinal, hematological, neurological and other toxicities, in patients who is diagnosed with lung cancer. Meta-analyses were conducted to determine the association between genetic polymorphisms and platinum-induced toxicity by checking odds ratio (OR) and 95% confidence interval (CI) using random or fixed-effects models as appropriate. Results: 17 eligible studies met the inclusion criteria with enough data were extracted and presented in a comprehensive way. A total of 14 polymorphisms from 9 genes were included for meta-analysis. MTHFR rs1801131 and MDM2 rs1690924 were significantly correlated with platinum-induced GI toxicity (P-value were 0.04 and 0.02 respectively). Carriers of MTHFR rs1801131AA and MDM2 rs1690924TC/CC genotype tended to have higher risk of GI toxicity than patients with other genotypes [OR = 1.73, 95% CI = 0.86-2.18; and OR = 0.51, and 95% CI = 0.29-0.88]. Compared with MTHFR rs1801133CC genotypes, carriers of CT/TT genotype had significantly increased risk of hematologic toxicity (P = 0.02, OR = 1.86, 95% CI 1.10-3.14]. Conclusion: More attention should be paid to MTHFR and MDM2 for personalized chemotherapy treatment among lung cancer patients in the future.